The Development of Agro-sociopreneurship through the Use of Biofloc Technology in Catfish Farming in Sukamakmur Village, Ajung District, Jember - Nurul Novikarumsari; Basuki Basuki; Indri Fariroh; Indah Ibanah (MITRA: Jurnal Pemberdayaan Masyarakat, 2022)
One problem faced by the community in Sukamakmur Village, Ajung District, East Java, is that its youth groups do not have a program to improve the community welfare. Another issue is the lack of public knowledge regarding the use of potential resources, including water resources. The newly established BUMDes and youth organization seem not to have any business programs, which has become an obstacle to the efforts to improve the welfare of the rural community. To address these problems, a community service program was conducted to assist the youth groups, karang taruna, by empowering them and developing agro-sociopreneurship. Given the abundant water resources, they can be used to apply the biofloc technology for catfish farming. The activities in the program included needs analysis using the ABCD analysis of the FGD sessions, education on agrosociopreneurship, training, monitoring, and evaluation. The result showed that through the agrosociopreneurship mentorship, (i) as many as 33% of karang taruna members and livestock farmers attempted to engage in agro-sociopreneurship and (ii) livestock farmers have been able to apply biofloc technology in catfish farming.